Self-Etching of Metal-Organic Framework Templates during Polydopamine Coating Nonspherical Polydopamine Capsules and Potential Intracellular Trafficking of Metal Ions - Ye, Zihan (Langmuir : the ACS journal of surfaces and colloids, 2017)
Traditionally, containers made from steel or other metals are not good for making tea, probably due to the fact that polyphenol components in tea can chelate with metal ions. A similar reason might stand behind the observations as reported herein. During the coating of well-defined metal-organic framework (MOF) crystalline particles with polydopamine (PDA) via pH-induced self-polymerization of dopamine, we found that MOF templates automatically etch off during the coating, giving rise to nonspherical PDA capsules that inherit the morphologies of the templates. Such self-etching of MOF templates is ascribed to the chelation of the metal nodes of the MOFs by the catechol moieties in the PDA layer. In addition, the self-etching of the zeolitic imidazolate framework-8 (ZIF-8) with a truncated cubic shape probably follows a crystalline facet-dependent fashion, resulting in intermediate yolk-shell structures with ZIF-8 cargos of various shapes inside a highly biocompatible PDA shell. Incubation of such intermediate hybrid particles with the cancerous HeLa cell line leads to pronounced cytotoxicity, which is tentatively connected with the cellular internalization of the ZIFPDA nanoparticles because of the cell affinity of the PDA layer. Subsequently, the continuous release of Zn2+ by the self-etching of the encapsulated ZIF-8 inside the cell increases intracellular Zn2+ to a harmful level. Therefore, intracellular delivery of metal ions is probably realized, which might offer a novel way for cancer therapy